Fleet enema: a straight up method of management in tar burn injuries - Farrah-Hani Imran; Mohamed Sam-Aan H; Enda K; Srijit Dass (Pusat Perubatan Universiti Kebangsaan Malaysia, 2020)
Tar burns though classified as a chemical injury, because of the difference in mechanism of injury and the difficulty in removing the agent from skin without causing further skin damage, presents a difficult problem to solve. More so, when paediatric patients are involved. Tar burns are usually an occupational injury in nature and are observed mostly in adult males. Here we present two cases, i.e. a six-year-old boy and a 15-year-old girl who sustained tar burns and were successfully treated with Fleet® Mineral oil enema and paraffin tulle Bactigras®, readily available in a hospital environment.